2015
DOI: 10.1177/0148607115606407
|View full text |Cite
|
Sign up to set email alerts
|

Shielding Parenteral Nutrition From Light Improves Survival Rate in Premature Infants

Abstract: Shielding PN from light has vital repercussions that call for action to provide photoprotected delivery systems and infusion sets in premature infants. Further studies should be extended to the increasing number of children and adults receiving long-term home PN to evaluate the effects of light protection on severe complications that impede their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 41 publications
0
33
0
9
Order By: Relevance
“…Some randomized controlled trials demonstrated a decrease in BPD by shielding PN from light, 36 , 37 while a recent one did not confirm this finding 38 . Recent meta‐analysis confirmed that adequate shielding of PN decreases mortality by half in extremely preterm infants 39 . The second possible intervention is to increase the activity of the glutathione antioxidant system.…”
Section: Discussionmentioning
confidence: 99%
“…Some randomized controlled trials demonstrated a decrease in BPD by shielding PN from light, 36 , 37 while a recent one did not confirm this finding 38 . Recent meta‐analysis confirmed that adequate shielding of PN decreases mortality by half in extremely preterm infants 39 . The second possible intervention is to increase the activity of the glutathione antioxidant system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the concern of cholestasis, fatty acid compositions of some ILE available in the United States do not meet the needs of the neonatal population aside from preventing essential fatty acid deficiency 19 . ‐ 21 Safety concerns, specifically risk of mortality, were reported in a meta‐analysis evaluating effects of not light protecting PN used for preterm infants 22 . Currently, adequate light protection may not be feasible, depending on the circumstances of whether PN is compounded on‐site or at a central location.…”
Section: Question 2: Are There Any Circumstances In Which Pn Is the Omentioning
confidence: 99%
“…However, our findings suggest caution in the introduction of SMOF in PN, waiting for more investigations. A recent meta‐analysis on photo‐protection of PN reported a reduction of the mortality by half in premature infants receiving PN . In clinical routine, an adequate protection against light exposure is very hard to achieve .…”
Section: Discussionmentioning
confidence: 99%
“…The Guinea pig has been frequently used in the last few years as a neonatal animal model of parenteral nutrition, especially for understanding the impact of PN or components of PN or oxidant molecules generated in PN on pulmonary oxidative stress deriving from free radicals or peroxides as well as on alveolarization . Several findings from this model have found a match in premature infants . In addition, its lipid metabolism is close to humans, and for this reason, it is proposed as a suitable model for lipid study …”
Section: Methodsmentioning
confidence: 99%